Design and development of six degrees of freedom articulated robot arm for painting - Priyandoko, Gigih; Romlay, Fadhlur Rahman Mohd; Rosli, Rosmazi; At-Tasneem, Mohd Amin (2017)
A three six of freedom (6DOF) articulated robot is a machine that would offer the opportunity to reduce or eliminate human exposure to difficult and hazardous environments in a painting process. This research is about to design and develop 6 DOF articulated robot arm to perform the painting process. Development of 6 degrees of freedom articulated painting robot is starting from the designing process, fabrication process and analysis for dynamic characteristics. Besides that another objectives of the project are to develop the control system of 6 DOF articulated robot and to generate the trajectory motion of the articulated robot in the flat surface. The parts of robots are base, arms and end effector. The robot moves in term of rotation of every joint. The performance of the robot is measured using dynamic characteristics such as the velocity, the acceleration and torque produced. The Lagrange Newton formulation is derived to obtain the velocity, acceleration and torque, while the structural analysis is conducted using finite element method. To sum up, the performance of the robot is determined by the dynamic characteristics and compare between the experimental value and theoretical value. A control system of 6 DOF and the trajectory motion of the end effector on a flat surface have been generated to perform the painting process. By using the inverse kinematics equation, the end effector coordinates needs to be assigns appropriately to generate the joint angles for each links of the articulated robot. So far, the result shows that the articulated robot is able to move on the flat surface by using the flat trajectory motion of the robot. Each coordinate of the end effector generated the joint angle of each links by using the inverse kinematics equation. The angular velocity of each links has been simultaneous to perform the painting process on the flat surface.